Research on water immersion damage characteristics and equivalent width of coal pillar - Zhixian Shi; Guangan Zhu; Zekai Zi (Scientific Reports)
Abstract Affected by weakening effect of water in the goaf, the bearing capacity of coal pillar reduced, and coal pillar rock burst is prone to occur, which is a serious threat to mine safety in production. In order to study the equivalent width and stability of coal pillar in water-rich coal seam, taking the section coal pillar of a working face as the research object, combined with laboratory test, theoretical analysis, simulation and engineering practice, the stress, elastic core area width, damage degree and energy accumulation of 36 m water-immersed coal pillar and 26 m, 28 m, 30 m, 32 m, 36 m unimmersed coal pillars are analyzed. The research results show that: (1) The reasonable width of coal pillar under flooded and unflooded conditions is 36.09 m and 29.58 m, respectively. The width has been reduced by 6.51 m under flooded condition. The peak stress value in the goaf and the side of the working face and the range of stress curve in the elastic core area are similar between 36 m water-immersed coal pillar and 30 m unimmersed coal pillar. The bearing capacity of the two is equivalent, which is consistent with theoretical analysis. (2) The coupling relationship between flooding and damage of coal pillar can be divided into three stages with the increase of iteration times. Firstly, the flooding area in the early stage of the coal pillar is the damage area caused by the excavation working face, and the flooding rate is fast. Secondly, the mechanical parameters of the coal pillar decrease after water immersion, resulting in the increase of the damage area of the coal pillar. In turn, water permeates into the coal pillar, and the rate of immersion is slower. Finally, the flooded area of the coal pillar remains unchanged from the damaged area. (3) After the 36 m coal pillar was immersed in water, the peak stress of the side coal pillar in the goaf decreased by 7.66%. And as the number of iterations increases, the distance of the coal pillar “wedge” high energy area is gradually shortened. The damage rate experienced three stages: rapid, slow, and stopped increasing. The bearing capacity of coal pillar decreases after water immersion softening (4) The widths of the elastic core areas in the upper, middle and lower parts of the 36 m water-immersed coal pillar and 30 m unimmersed coal pillar are 20, 14.5, 12 m and 18, 14, 11 m respectively, which are relatively close and greater than the critical width of the coal pillar. The actual damage degree of both is greater than the critical damage degree. The elastic strain energy densities of coal pillars are 191 and 187 kJ/m3, respectively, showing wedge-shaped distribution. The carrying capacity of 36 m water-immersed coal pillar and 30 m unimmersed coal pillar is equivalent and stable. (5) Under the geological condition, the energy accumulation and distribution form of coal pillar with a width less than 30 m is “cup-shaped”. The risk of rock burst is higher. When the coal pillar is greater than 30 m, coal pillar energy is distributed in two “wedges”. The stability of coal pillar is enhanced, The risk of rock burst is reduced. The research can provide a reference for determining the reasonable width of section coal pillar in the water-rich rock burst coal seam in Binchang mining area.